Changes in TRG/ApoA-1 ratio, TRG/HDL-C ratio and lipid serum profile after combination therapy with telmisartan/amlodipine in prediabetic patients. (11th May 2022) - Liontos, A; Papathanasiou, A; Biros, D; Papagiannopoulos, C; Tsourlos, S; Athanasiou, L; Zarachi, A; Kolios, NG; Pargana, E; Nasiou, M; Christaki, E; Liberopoulos, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction-Purpose: The combination of telmisartan with amlodipine is a commonly administered combination of an agonist ATII (angiotensin receptor II) and CCB (calcium channel blocker) for the management of hypertension. The purpose of this study is to evaluate the effect of the fixed of combination telmisartan/amlodipine 80/5mg per day on the levels of serum lipids, as well as the levels of serum apolipoproteins and the TRG/ApoA-1, TRG/HDL-C ratios, in patients with stage 2 hypertension (systolic blood pressure (SBP) 160-180 mmHg and/or diastolic blood pressure (DBP) 100-110 mmHg) and with prediabetes (IFG/IGT), before and after the 3-month treatment. Methods: Data from 51 patients who had visited our outpatient clinic for lipid metabolism disorders during the period 2014-2018 and had been randomized in the telmisartan/amlodipine group 80/5mg per day. The patients (35 male/16 female) had BMI: 29.32 [27.37-31.65]. The levels serum lipids and of apolipoproteins B, A1, Lp(a) and E were measured before the beginning of the treatment and 3-months after its administration. Results: The resulting variations of SBP and DBP levels before and after the 3-month treatment, as well as the variations of serum lipid, apolipoprotein levels and TRG/ApoA-1, TRG/HDL-C ratios are presented on Table 1. Conclusion: The 3-month telmisartan/amlodipine therapy seems to improved, statistically significant both SBP and DBP levels (decreased by -13.58 % and -13 % respectively, p<0.001, for both values). Serum lipid levels didn't show any significant variation before and after treatment. Statistically significant changes were not present in apolipoprotein levels, also. Finally, there were no statistically significant variations in either TRG/ApoA-1 or TRG/HDL-C ratios.